Oral health status and behaviour among Kanikkaran tribes of Mundandhurai Hills in Tirunelveli district, Tamil Nadu - Rahmath Meeral P; Arthi Balasubramaniam; Meignana Arumugham Indiran; Karthik M (Elsevier, 2024)
Background: Kanikkaran are semi-nomadic tribes inhabiting Mundandhurai hills in Tamil Nadu. Their traditional method of maintaining oral health, seclusion, ignorance, and limited access to dental resources has led to their poor oral health situation. Thus, the present study is designed to assess the oral health status of the Kanikkaran tribals residing in Mundandhurai Hill of Tirunelveli district. Methods: A cross-sectional epidemiological study was conducted among 907 Kanikkaran tribes in Mundandhurai hills. Mundandhurai Hills in Ambasamudram taluk of Tirunelveli district was selected by convenience method. World Health Organization (WHO) oral health assessment form and its self-oral health assessment form (2013) were used. Descriptive and inferential statistics were performed using SPSS version 23.0. Result: There is a significant negative moderate correlation between age and dental caries (r = −0.752). There is a significantly high risk among tribes with the primary school of education and agriculture as an occupation for periodontal disease (OR = 3.48), premalignant lesion (OR = 2.52), and non-carious dental lesions (OR = 3.14). Males with primary school education and agriculture as occupation had a significantly higher consumption of sugar and use of tobacco (p < 0.05). Conclusion: Primary school of education with agriculture/labor as occupation had a high prevalence of DMFT, periodontitis, premalignant, and non-carious dental lesions. The results of the present study punctuate the necessity of raising awareness of the significance of good oral health through education and implementation of necessary dental services in Kanikkaran tribes.